Pre-operative assessment of difficult laparoscopic cholecystectomy: a scoring method - Malligurki, Vamsi K.; A., Bhaskaran (International Surgery Journal, 2021)
Background: Laparoscopic cholecystectomy (LC) has become the gold standard procedure for management of symptomatic gallstone disease. At times, it is difficult and takes longer time or has to be converted to an open procedure. The study was undertaken to determine the factors which predict difficult LC. The aim of the study was to evaluate a pre-operative scoring method to predict difficult LC. Methods: This was a prospective study conducted in the department of general surgery, MVJ Medical College, Bangalore from December 2020 to August 2021. There were 100 cases operated by experienced surgeons. Scoring method which included parameters from history, clinical and sonological findings with maximum score up to 15. Score up to 5 predicted easy, 6-10 difficult and 11-15 is very difficult. Results: Pre-operative scoring system correlated with 85.7% for easy, 83.3% in difficult cases and 100% in very difficult cases. The factors like previous history of hospitalization (p=0.004), clinically palpable gallbladder (GB) (p=0.009), impacted GB stone (p=0.001), pericholecystic collection (p=0.04), and abdominal scar due to previous abdominal surgery (p=0.009) were found statistically significant in predicting difficult LC. Conclusions: Pre-operative prediction of risk factors to assess the operative difficulty is an important point for planning the surgery and the high-risk patients may be informed accordingly.